Responsabilité sociale des entreprises et diversité des capitalismes - Michel Capron; Pascal Petit (Revue de la Régulation)
A survey of the literature on corporate social responsibility allows in the first half of the paper to distinguish three phases. The ethic goals of the first phase have first been replaced by utilitarian considerations in a second phase then followed by the will to assess in terms of sustainable development the activity of the firms in respectively the environmental, social and economic fields. In the second part of the paper one has tried, on the basis of six surveys done by the audit firm KPMG between 1993 and 2008, to analyze the process of institutionalization of the non financial reporting by large listed firms. Here again one distinguishes two periods. One is largely geered by the fear of a worldwide public opinion over the environmental hazards. It concerns more specifically certain sectors. The second period follows after year 2000 the rising importance of financial criteria in the governance of the firms. Non financial reporting becomes an obligation for all listed firms. What will become of this practice afterwards will depend on both the diffusion of certification procedures and the extension of this practice of reporting among medium and small firms. Several scenarios for this “third” phase are analyzed in conclusion which all stress the importance of the type of capitalism under view.